Penerapan Promotion Mix pada Bisnis Sate Banyumas Sagulung - Batam - Yuswardi, Yuswardi; Ananda, Anggun Dea (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Promotion mix, in a marketing context, is a collection of strategies and tactics used by companies to communicate the value of their products or services to target markets. It plays a central role in business strategy as it allows companies to build brand awareness, attract the attention of potential customers, and motivate purchasing actions. The main components of the promotion mix include advertising, personal selling, sales promotion, public relations, and direct marketing tools. This community service activity was carried out at the Sate Banyumas business to further increase sales and business development.